2022
DOI: 10.1007/s11427-021-2137-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of phenylalanine ammonia lyase as an intracellularly free and extracellularly cell surface-immobilized enzyme on a gut microbe as a live biotherapeutic for phenylketonuria

Abstract: Phenylketonuria (PKU), a disease resulting in the disability to degrade phenylalanine (Phe) is an inborn error with a 1 in 10,000 morbidity rate on average around the world which leads to neurotoxicity. As an potential alternative to a protein-restricted diet, oral intake of engineered probiotics degrading Phe inside the body is a promising treatment, currently at clinical stage II (Isabella, et al., 2018). However, limited transmembrane transport of Phe is a bottleneck to further improvement of the probiotic’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“… Jiang et al (2023) revealed that EPs with membrane-associated and intracellular PAL decreased serum Phe levels in the PKU mouse model when the enzyme was expressed in EcN. In a similar animal study by Durrer et al (2017) , the oral administration of PAL-producing EP to the PKU mouse model significantly reduced blood Phe levels.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“… Jiang et al (2023) revealed that EPs with membrane-associated and intracellular PAL decreased serum Phe levels in the PKU mouse model when the enzyme was expressed in EcN. In a similar animal study by Durrer et al (2017) , the oral administration of PAL-producing EP to the PKU mouse model significantly reduced blood Phe levels.…”
Section: Resultsmentioning
confidence: 88%
“…The included studies used EcN (n=5), Lactobacillus plantarum (n=1), and L. reuteri (n=1) as hosts and manipulated them to produce intracellular (n=6) or secretory (n=1) recombinant proteins. Jiang et al (2023) revealed that EPs with membrane-associated and intracellular PAL decreased serum Phe levels in the PKU mouse model when the enzyme was expressed in EcN. In a similar animal study by Durrer et al (2017), the oral administration of PAL-producing EP to the PKU mouse model significantly reduced blood Phe levels.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Genetically engineered EcN has shown promising application as living therapeutic in treating colitis, colorectal cancer and metabolic disease [35][36][37][38][39][40][41] . EcN has also been used as a vehicle for delivering the type II CRISPR-Cas systems to kill pathogens in animal models 42 .…”
Section: Introductionmentioning
confidence: 99%